Yeast β-glucan, a potential prebiotic, showed a similar probiotic activity to inulin. Issue 12 (24th November 2020) - Wang, Huali; Chen, Guijie; Li, Xiang; Zheng, Fuping; Zeng, Xiaoxiong
Abstract : β-Glucan, an economical by-product of yeast, showed a similar probiotic activity to inulinw, which is expected to be a potential prebiotic for the modulation of gut microbiota. Abstract : β-Glucan, an economical by-product of yeast, has various health-promoting activities. However, the digestion and fermentation characteristics of β-glucan from yeast are still unknown. Thus, simulated digestion under saliva, gastric and small intestinal solutions and fermentation by gut microbiota were studied in this work. The results showed β-glucan could not be hydrolyzed in saliva, gastric and small intestinal conditions. Then, β-glucan reaches the large intestine, where it is degraded and metabolized by gut microbiota. At the same time, β-glucan could modulate the structure and composition of gut microbiota by inhibiting the proliferation of harmful gut microbiota and promoting the growth of health-promoting gut microbiota. At the phylum level, β-glucan significantly decreased the ratio of Firmicutes to Bacteroidetes. Furthermore, both β-glucan and inulin could selectively promote the growth of Bifidobacterium . Unlike inulin, β-glucan was able to better promote the growth of Bifidobacterium_longum . Thus, β-glucan showed a similar probiotic activity to inulin and is expected to be a potential prebiotic for the modulation of gut microbiota.